A Veteran Special Education Teacher and a General Education Social Studies Teacher Model Co-teaching: The CoPD Model - Thomas-Brown, Karen A.; Sepetys, Peggy (Journal of the American Academy of Special Education Professionals, 2011)
This research explores using participant ethnography, the theoretical and practical underpinnings of the combination pedagogical approach of co-teaching and embedded professional development within the Co-teaching Professional Development Approach (CoPD). The structure of this approach is presented and the research findings examine the outcomes of this approach within the context of two general education social studies classrooms. The findings indicate that CoPD offers a suitable approach to accommodating with students with disabilities in a specific general educational setting while demonstrating the potential content knowledge benefits to special educators, the pedagogical benefits to the general educators and the academic and social benefits to students with disabilities.